Loneliness in College Students: How is the Role of Adjustment and Social Support? - Asiyah Khoirun Nisa; Sri Lestari (Jurnal Psikologi Teori dan Terapan, 2023)
Loneliness is one of the problems experienced by students because of the lack of social support and not being matched by the ability to adapt to the social environment. The purpose of this study was to empirically test the role of adjustment and social support together in loneliness. Two hundred students aged 18-25 in Solo Raya participated in this survey. The participants get through incidental sampling techniques. The instruments used were the loneliness, self-adjustment, and social support scales. Data were analyzed using multiple linear regression. The results show that adjustment and social support together affect loneliness. Partially self-adjustment and social support have an equal effect on loneliness in college students. The results of this study imply that the availability of social support from the immediate environment can help students overcome loneliness among students. ABSTRAK Kesepian menjadi salah satu problem yang dialami mahasiswa karena minimnya dukungan sosial dan tidak diimbangi dengan kemampuan untuk menyesuaikan diri dengan lingkungan sosial. Tujuan penelitian ini untuk menguji secara empiris peran penyesuaian diri dan dukungan sosial secara bersama-sama terhadap kesepian. Survei dilakukan kepada 200 mahasiswa usia 18-25 tahun di Solo Raya yang direkrut melalui teknik sampling incidental. Instrumen yang digunakan meliputi skala kesepian, skala penyesuaian diri, dan skala dukungan sosial. Analisis data yang digunakan yaitu regresi linear berganda. Hasil penelitian menunjukkan penyesuaian diri dan dukungan sosial secara bersama-sama berperan signifikan terhadap kesepian. Secara parsial penyesuaian diri dan dukungan sosial memiliki pengaruh yang setara terhadap kesepian pada mahasiswa. Implikasi hasil penelitian ini adalah ketersediaan dukungan sosial dari lingkungan terdekat dapat membantu mahasiswa untuk mengatasi kesepian pada mahasiswa.